MEMBANGUN GREEN LOYALTY MELALUI GREEN TRUST DAN GREEN CORPORATE IMAGE - Purnomo, Nanto (Ekonomi dan Bisnis: Berkala Publikasi Gagasan Konseptual, Hasil Penelitian, Kajian, dan Terapan Teori, 2024)
In this modern era, consumers express a desire to buy environmentally friendly products with the aim of preserving the earth. Currently, the concept of green marketing is used as a trust issue by companies as part of their marketing strategy to attract customer attention. The commitment and concern for the environment shown by Aqua is a form of green marketing. This research applies a survey method in a quantitative approach. Data analysis was carried out using Smart PLS 3.0 software. The findings from the research show that there is a significant influence of the green trust variable (X1) on green loyalty (Y) in Aqua bottled drinking water products. Apart from that, there is a significant influence of the green trust variable (X1) on green satisfaction (Z) with Aqua bottled drinking water products. The green company image variable (X2) also has a significant influence on green loyalty (Y) for Aqua bottled drinking water products, and green company image (X2) also has a significant influence on green satisfaction (Z) for Aqua bottled drinking water products. Furthermore, green satisfaction (Z) also has a significant effect on green loyalty (Y) for Aqua bottled drinking water products. Apart from that, there is a significant influence on the green trust variable (X1) on green loyalty (Y) through green satisfaction (Z) on Aqua bottled drinking water products, and green company image (X2) also has a significant influence on green loyalty (Y ) through green satisfaction (Z) in Aqua bottled drinking water products.